2021
DOI: 10.1186/s13018-020-02174-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining the stability of minimally displaced lateral humeral condyle fractures in children: ultrasound is better than arthrography

Abstract: Background Evaluating of the articular cartilage status of the distal humeral epiphysis is difficult. Ultrasound imaging of the elbow is increasingly being used to confirm the integrity of the articular cartilage of minimally displaced lateral humeral condyle fractures in children with minimally displaced fractures. The aims of this study were to assess the correlations between ultrasound and arthrography findings for predicting the integrity of the cartilage hinge and to describe the utility o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The lateral condyle fracture of the humerus is the second most frequent elbow fracture in children. Ultrasound technology has become extremely popular clinically, given its convenience, non-invasiveness, and ability to visualize neurovascular and soft tissues ( 4 ). Kirschner wire fixation with ultrasound localization represents a more effective approach consistent with the contemporary concept of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral condyle fracture of the humerus is the second most frequent elbow fracture in children. Ultrasound technology has become extremely popular clinically, given its convenience, non-invasiveness, and ability to visualize neurovascular and soft tissues ( 4 ). Kirschner wire fixation with ultrasound localization represents a more effective approach consistent with the contemporary concept of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, arthrography requires repeated x-ray fluoroscopy, which increases the risk of iatrogenic radiation damage and is an invasive procedure with hazards such as allergies to contrast agents. In recent years, ultrasound has been widely employed in treating lateral condyle fractures in children due to its ability to visualize cartilage hinges, properly determine re-displacement risk, and avoid iatrogenic harm ( 4 , 5 ). Therefore, the clinical efficacy of percutaneous Kirschner wire fixation for children with Jacob II and III fractures of the lateral humeral condyle under ultrasound localization was assessed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…It still a big challenge for orthopedic pediatricians and radiologists. For better diagnosis and treatment in HLCFs, some studies tried to use modified radiograph projection, high-frequency ultrasound or arthrography to improve the accuracy of HLCFs' diagnosis, but each examination had its own limitations, and the results were also inconsistent [ 2 4 ]. MRI has the advantages of high resolution of soft tissues, multi-directional, multi-parameter imaging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the recent publication by Wu and colleagues [1]. Weiss et al [2] defined a classification system and treatment for lateral humeral condyle fractures (LHCF) based on fracture displacement and articular congruity: Bernthal et al [3] reported on 141 LCHFs, 76 treated non-operatively, 14 with CRPP and 51 with ORIF.…”
mentioning
confidence: 99%
“…Li et al [5,6] being the same authors as Wu et al [1] previously reported that the lateral humeral cartilage hinge and fracture stability can be accurately determined with transverse ultrasound (US), based on US examinations performed on children with LHCFs treated between February 2013 and May 2019, without the need for arthrograms.…”
mentioning
confidence: 99%